Thematic Analysis of the Health Records of a National Sample of US Veterans With Advanced Kidney Disease Evaluated for Transplant - Butler, Catherine R. (JAMA Intern Med, 2020)
IMPORTANCE: To be considered for a kidney transplant, patients with advanced kidney disease must participate in a formal evaluation and selection process. Little is known about how this process proceeds in real-world clinical settings. OBJECTIVE: To characterize the transplant evaluation process among a representative national sample of US veterans with advanced kidney disease who were referred to a kidney transplant center. DESIGN, SETTING, AND PARTICIPANTS: This qualitative study was a thematic analysis of clinician notes in the electronic health records of US veterans referred for kidney transplant evaluation. In a random sample of 4000 patients with advanced kidney disease between January 1, 2004, and December 31, 2014, cared for in the US Department of Veterans Affairs (VA) health care system, there were 211 patients who were referred to a transplant center during the follow-up period. This group was included in the qualitative analysis and was followed up until their date of death or the end of the follow-up period on October 8, 2019. MAIN OUTCOMES AND MEASURES: Dominant themes pertaining to the kidney transplant evaluation and selection process identified through thematic analysis. RESULTS: Among 211 study patients, the mean (SD) age was 57.9 (9.5) years, and 202 patients (95.7%) were male. The following 4 dominant themes regarding the transplant evaluation process emerged: (1) far-reaching and inflexible medical evaluation, in which patients were expected to complete an extensive evaluation that could have substantial physical and emotional consequences, made little accommodation for their personal values and needs, and impacted other aspects of their care; (2) psychosocial valuation, in which the psychosocial component of the transplant assessment could be subjective and intrusive and could place substantial demands on patients’ family members; (3) surveillance over compliance, in which the patients’ ability and willingness to follow medical recommendations was an important criterion for transplant candidacy and their adherence to a wide range of recommendations and treatments was closely monitored; and (4) disempowerment and lack of transparency, in which patients and their local clinicians were often unsure about what to expect during the evaluation process or about the rationale for selection decisions. For the evaluation process to proceed, local clinicians had to follow transplant center requirements even when they believed the requirements did not align with best practices or the patients’ needs. CONCLUSIONS AND RELEVANCE: In this qualitative study of US veterans with advanced kidney disease evaluated for transplant, clinician documentation in the medical record indicated that, to be considered for a kidney transplant, patients were required to participate in a rigid, demanding, and opaque evaluation and selection process over which they and their local clinicians had little control. These findings highlight the need for a more evidence-based, individualized, and collaborative approach to kidney transplant evaluation.